Insights, attitudes, and perceptions about asthma and its treatment: a multinational survey of patients from Europe and Canada. Issue 1 (December 2016) - Sastre, Joaquin; Fabbri, Leonardo; Price, David; Wahn, Hans; Bousquet, Jean; Fish, James; Murphy, Kevin; Sears, Malcolm
Abstract Background Asthma surveys completed within the past 10 years in the Americas and the Asia-Pacific region have shown significant underassessment of asthma severity in addition to undertreatment of asthma and have suggested the need to improve long-term asthma management. In this study, we examined the frequency of asthma symptoms and severe episodes, patients' perceived asthma control, and use of asthma medications in Europe and Canada. Methods The Asthma Insight and Management survey (54 questions) was conducted in Europe (Germany, Italy, Spain and the United Kingdom) and Canada from June 14 through July 28, 2010. Telephone interviews were conducted with randomly screened patients or parents of adolescents (aged 12–17 years) with asthma; patients younger than 12 years of age were excluded from the survey. Responses were reported separately for each country and in total for all five countries. Results Seventy-five thousand three hundered thirty-five households were screened, and 2003 patients were interviewed. The survey respondents represented a wide range of severity. Overall, 26 % of patients reported symptoms daily or most days over the past 4 weeks, but most patients (81 %) perceived their asthma to be well or completely controlled. Over the past year, 41 % of patients had episodes of frequent/severe symptoms, and 50 % reported acute treatment (e.g. hospitalization, emergency visit, unscheduled physician visit) for asthma. Across countries, 52 % of patients reported taking controller medication every day over the past year, 27 % reported not taking any controller medication, and 14 % reported stopping controller treatment for 3 months or longer the last time they stopped. Many patients considered asthma well controlled if each year they had only two urgent doctor visits (50 %), three or four exacerbations (60 %), and/or one emergency room visit (41 %). Discussion This is the largest survey of patients with asthma in Europe and Canada in more than a decade. Conclusion In 2010, many surveyed patients in Europe and Canada reported features indicating uncontrolled asthma, yet the majority believed they were well controlled, indicating that they had low expectations of long-term asthma management. Use of controller medications was substantially less than recommended in treatment guidelines.